The Influence of Ozonation Carried Out during Vegetation on the Content of Selected Bioactive Phytochemicals and the Microbiological Load of Tubers of Raphanus sativus var. sativus - Miłosz Zardzewiały; Natalia Matłok; Tomasz Piechowiak; Maciej Balawejder (Agriculture, 2023)
The aim of the study was to determine the effect of ozone gas fumigation on the mechanical, chemical, and microbiological parameters of radish tubers. Radish plants were grown in the ground in accordance with the principles of good agricultural practice and condition suitable for the soil and climatic conditions of south-eastern Poland. At the end of the growing season, 24 h before harvest, radish plants were exposed to a variable factor, i.e., fumigation with ozone gas at various doses (1 ppm for 1 and 5 min; 5 ppm for 1 and 5 min) in order to modify selected metabolic pathways of bioactive compounds. Then, 24 h after ozonation, radish tubers were harvested and placed in a climatic chamber with controlled conditions, i.e., 2 °C and 90% humidity. Laboratory analyses were performed during storage on days 1, 5, and 10. The ozonation used did not significantly improve the mechanical properties and water content of radish tubers. There was a beneficial effect of selected gaseous ozone doses (1 ppm for 1 and 5 min; 5 ppm for 1 min on the 10th day of storage) on the biosynthesis of selected bioactive compounds, i.e., ascorbic acid content, total polyphenol content, and antioxidant potential during storage. The most beneficial effects of the use of gaseous ozone were observed in the storage process in reducing the microbiological load of radish tubers. Among the ozonation doses used, the dose of 5 ppm for 5 min had the most beneficial effect on reducing the microbiological load. It reduced the number of yeasts and molds by 14.2% and aerobic mesophilic bacteria by 20.9% compared to the control sample on the last day of storage. Additionally, between the 5th and 10th day of storage, a significant effect of each ozone dose applied on reducing the occurrence of yeasts, molds, and mesophilic aerobic bacteria during tuber storage was noted.